Mosques and Economic Empowerment of The Ummah - Ritonga, Anas Habibi; Wijaya, Muhamad Rudi (Fakultas Dakwah dan Ilmu Komunikasi, 2022)
The mosque is one of the main places for Muslims in the world, not the case in Indonesia. This is because most Muslims carry out their activities in the mosque. At the time of the Prophet Muhammad the mosque functioned as the center of government, financial center, training center, security, security, etc., but nowadays most of it is only used as a place of worship. The view that the mosque is only seen as a place of worship for the mahdah cannot be released to encourage the improvement of the welfare of the people in the mosque and its surroundings through empowerment, and to assist the local government in the vicinity. Since the time of the Prophet, the mosque has become one of the centers for the development of funds, both zakat infaq and shodaqoh which are used for welfare and even as community baitulmal as a means of collecting funding. The facility has secured one of the financial bases that can guarantee survival. Helping to get involved in the local economy as well as the financial freedom of the mosque.